Soy Isoflavones in the Management of Postmenopausal Osteoporosis - Atmaca, Ayşegül; Kleerekoper, M.; Bayraktar, M.; Küçük, O. (Lippincott Williams & Wilkins, 2008)
This is a review article designed to address the effects of soy isoflavones on bone metabolism in postmenopausal women and their place in the prevention and treatment of postmenopausal osteoporosis. Soy isoflavones are natural products that could be used as an alternative to menopausal hormone therapy because they are structurally and functionally related to 17β-estradiol. In vitro and animal studies have shown that they act in multiple ways to exert their bone-supporting effects. They act on both osteoblasts and osteoclasts through genomic and nongenomic pathways. Epidemiological studies and clinical trials suggest that soy isoflavones have beneficial effects on bone mineral density, bone turnover markers, and bone mechanical strength in postmenopausal women. However, there are conflicting results related to differences in study design, estrogen status of the body, metabolism of isoflavones among individuals, and other dietary factors. The long-term safety of soy isoflavone supplements remains to be demonstrated. Copyright © 2008 The North American Menopause Society.
Keywords: Bone Mineral Density; Menopause; Osteoporosis; Phytoestrogens; Soy Isoflavones